Resources and facilitators of workplace well-being among healthcare professionals in a hospital setting—results of a qualitative interview study - Berschick, Julia; Czakert, Judith; Koch, Anna Katharina; Schröter, Marleen; Steinmetz, Melanie; Bogdanski, Martin; Schiele, Julia Katharina; Kessler, Christian; Seifert, Georg; Stritter, Wiebke (Frontiers in Public Health, 2025)
BackgroundWorking in a hospital setting can be rewarding but also represents a demanding and often stressful work environment due to personnel shortage and high work volumes among others. A considerable body of literature addresses the adverse effects of working conditions that often result in poor well-being of medical professionals. This work moves from a problem-centered approach towards resilience-focused pathways. It does so by focusing on (self-reported) individual and organizational resources and facilitators of workplace well-being through medical professionals’ ability to perceive and engage with capacities within a demanding work environment.MethodsThis paper is based on a qualitative study in which data was collected in two different German hospitals through interviews with medical doctors, nurses and medical assistants. Data was analyzed through inductive-deductive qualitative content analysis.ResultsOur findings show a variety of resources in 4 domains overarching individual solution-oriented mindset constitutions, success-driven behaviors, sense of meaning as well as resource-enhancing environmental factors. Healthcare professionals show diverse individual strategies and behavioral patterns to build resilience and foster proactive approaches to deal with challenges and high-pressure situations.ConclusionBeneficial influencing factors could be identified that reveal underlying processes and opportunities to prevent negative health-related outcomes. The findings provide valuable insights into specific individual coping strategies and attitudes that appear to be associated with resourcefulness. Information is provided to institutionally and individually support a successful management of a health professionals’ work life.